2021
DOI: 10.3390/nu13124315
|View full text |Cite
|
Sign up to set email alerts
|

Differential and Synergistic Effects of Low Birth Weight and Western Diet on Skeletal Muscle Vasculature, Mitochondrial Lipid Metabolism and Insulin Signaling in Male Guinea Pigs

Abstract: Low birth weight (LBW) offspring are at increased risk for developing insulin resistance, a key precursor in metabolic syndrome and type 2 diabetes mellitus. Altered skeletal muscle vasculature, extracellular matrix, amino acid and mitochondrial lipid metabolism, and insulin signaling are implicated in this pathogenesis. Using uteroplacental insufficiency (UPI) to induce intrauterine growth restriction (IUGR) and LBW in the guinea pig, we investigated the relationship between UPI-induced IUGR/LBW and later lif… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 110 publications
0
7
0
Order By: Relevance
“…The highly expressed tsRNAs were mainly involved in the biological process of embryonic development and cell connection, and most significantly enriched pathways were GnRH signaling pathway, insulin signaling pathway, MAPK signaling pathway, melanogenesis, and focal adhesion signaling pathways. The GnRH signaling pathway ( Korpysz and Szalecki, 2019 ), insulin signaling pathway ( Dunlop et al, 2021 ), and MAPK signaling pathway ( Choi et al, 2020 ) have been reported to be associated with IUGR. In addition, differentially expressed tsRNAs in normal-size and IUGR porcine skeletal muscle were mainly enriched in metabolic pathways, Rap1 signaling pathway, endocytosis, mTOR signaling pathway, and AMPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The highly expressed tsRNAs were mainly involved in the biological process of embryonic development and cell connection, and most significantly enriched pathways were GnRH signaling pathway, insulin signaling pathway, MAPK signaling pathway, melanogenesis, and focal adhesion signaling pathways. The GnRH signaling pathway ( Korpysz and Szalecki, 2019 ), insulin signaling pathway ( Dunlop et al, 2021 ), and MAPK signaling pathway ( Choi et al, 2020 ) have been reported to be associated with IUGR. In addition, differentially expressed tsRNAs in normal-size and IUGR porcine skeletal muscle were mainly enriched in metabolic pathways, Rap1 signaling pathway, endocytosis, mTOR signaling pathway, and AMPK signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the profiles of neutral lipid species in NEFA-treated BeWo trophoblasts were analyzed via Thin Liquid Chromatography coupled to Flame Ionization Detection (TLC-FID) as previously described [ 66 ]. In brief, collected lipid samples were dried under a gentle stream of N 2 gas and resuspended in 100% chloroform.…”
Section: Methodsmentioning
confidence: 99%
“…Its essence lies not only in ensuring longevity and robust bone mass but also in maintaining quality. Intriguingly, medical research has underscored that a staggering 99% of calcium accumulates in the skeletal system, fortifying the foundation of our framework [17], [18]. Nevertheless, the importance of age-appropriate calcium intake must be noticed, as children require distinct levels of supplementation compared to adults and older individuals.…”
Section: Minerals and Vitamins' Impact On Childhood And Adolescent Bo...mentioning
confidence: 99%
“…Furthermore, low calcium content can impact other essential nutrients, such as zinc, affecting its absorption and supplementation [20]. The timing of calcium supplementation in healthy children and infants also emerges as a relevant factor, revealing that it is most beneficial when they become prone to osteoporosis or experience low calcium intake [17]. Surprisingly, studies have suggested that a low calcium diet in rural Gambian children led to higher bone mineralization and density [17].…”
Section: Minerals and Vitamins' Impact On Childhood And Adolescent Bo...mentioning
confidence: 99%
See 1 more Smart Citation